Russia$1 (Bs Role in the Contemporary International Agri-Food Trade Systems - Wegren, Stephen K.; Nilssen, Frode; Wegren, Stephen K.; Nilssen, Frode (Springer Nature, 2022)
This Open Access book analyses the emergence of Russia as a global food power and what it means for global food trade. Russia's strategy for food production and trade has changed significantly since the end of the Soviet period, and this is the first book to take account of Russia's rise as a food power and the global implications of that rise. It includes food trade policy and practice, and developments in regional food trade. This book will be of interest to academics and practitioners in agricultural economics, international trade, and international food trade.
English
Keywords: International economic & trade law; Agricultural science; Agri-Food Trade Policy; Russia and World Trade; International Food Trade System; World Grain Trade; Globalism; Global Food Market; Regional food trade; Open Access